Aplikasi Pencatatan Perhitungan Laba Rugi Berbasis Desktop pada PT. Fachri Syafii Akbar - Akhsani Taqwiym; Nurasiah Nurasiah (ISB Atma Luhur, 2020)
Application of profit and loss is implemented from the problems that occur at PT. Fachri Syafii Akbar where in the PT there was a problem in recording the report so that sometimes the contents of the report did not match the recording in the admin section and expenditure in the field. This application was created to assist in the process of recording activity reports in the process of completing a project of PT Fachri Syafii Akbar so that there is no difference in the final report, otherwise the application will display the entire history of transactions in and out of transactions during the project. The methodology used is the waterfall method and the implementation of the needs analysis. From the results of field observations, an information flow design was obtained which was then implemented by making a program using Microsoft Visual Basic.Net 2013 and MySQL. The results achieved are the creation of a periodic application in recording the process of project completion activities until the final report.